Recommendations to dentists - the individual entrepreneur in the organization of medical activity (LLC "Endo Press", 2020)
Health care reform in recent years is accompanied by the development of market relations in all sectors of health care, and, first of all, in dentistry. All over the world, dentistry, regardless of the accepted health care system, has the largest volume of paid services. In the Russian Federation, a network of private dental organizations is widely available, offering paid dental services to the population. In the article we suggest, is considered the sanitary and epidemiological requirements that have to be fulfilled to open a private dental office and obtain a license for medical activities for the provision of dental services.